Development of earthquake energy demand spectra - Dindar, Ahmet Anıl; Yalçın, Mehmet Cem; Yükse, Ercan; Özkaynak, Hasan; Büyüköztürk, Oral (Earthquake Engineerıng Research Inst, 499 14Th St, Ste 320, Oakland, Ca 94612-1934 Usa, 2015)
Current seismic codes are generally based on the use of response spectra in the computation of the seismic demand of structures. This study evaluates the use of energy concept in the determination of the seismic demand due to its potential to overcome the shortcomings found in the current response spectra based methods. The emphasis of this study is placed on the computation of the input and plastic energy demand spectra directly derived from the energy-balance equation with respect to selected far-field ground motion obtained from Pacific Earthquake Engineering Research (PEER) database, soil classification according to National Earthquake Hazards Reduction Program (NEHRP) and characteristics of the structural behavior. The concept and methodology are described through extensive nonlinear time history analyses of single-degree-of-freedom (SDOF) systems. The proposed input and plastic energy demand spectra incorporate different soil types, elastic perfectly plastic constitutive model, 5% viscous damping ratio, different ductility levels, and varying seismic intensities.
Keywords: Seismicity regions; Ground motions; Input spectra